Predictive Laboratory Findings of Lower Extremity Amputation in Diabetic Patients: Meta-analysis. (December 2017) - Kim, Jong-Lim; Shin, Jin Yong; Roh, Si-Gyun; Chang, Suk Choo; Lee, Nae-Ho
Lower extremity amputation is a source of morbidity and mortality among diabetic patients. This meta-analysis aimed to identify significant laboratory data in patients with diabetic foot ulcer with high rates of lower extremity amputation. We performed a systematic literature review and meta-analysis using MEDLINE, EMBASE, and Cochrane databases. We extracted and evaluated 11 variables from the included studies based on amputation rates. This study used the Newcastle-Ottawa Scale to assess the quality of the studies. The search strategy identified 101 publications from which we selected 16 articles for review. We identified HbA1c, fasting blood glucose, white blood cells, C-reactive protein, and erythrocyte sedimentation rate as predictive variables of higher major amputation rate. Although further investigation of long-term and prospective studies is needed, we identified 5 variables as predisposing factors for higher major amputation in diabetic patients through meta-analysis.